Analisis Kendala Peserta Didik Dalam Pembelajaran Biologi Pada Masa Transisi (Daring Ke Luring) Di SMA Negeri Se-Kabupaten Toraja Utara - Todingan, Ajeng Klarica; Hiola, Fatmah; Dian Dwi Putri Ulan Sari Patongai; Abd. Muis (Jurnal Pendidikan Biologi Undiksha, 2023)
This research aims to determine the obstacles faced by students in learning biology during the transition period in North Toraja Regency State High Schools. This research was conducted in the even semester of the 2022/2023 academic year. This type of research is quantitative descriptive research by distributing questionnaires related to the obstacles faced by students during biology learning during the transition period (online to offline). The population in this study was 2152 students in classes X and XI Science consisting of 10 high schools in North Toraja Regency. The sampling technique was carried out using cluster sampling based on regional divisions so that 4 schools were obtained representing each regional division. Determining the minimum sample size uses the Slovin formula to obtain results of 300 samples. The results of the analysis show that students' obstacles in learning biology during the transition period (online to offline) reached a percentage of 50% in the moderately constrained category.